Synchronous AML and pancreatic neuroendocrine neoplasm, both successfully treated with somatostatin analogs and decitabine. Issue 1 (17th June 2022) - Ehsanullah, Syed; Trikalinos, Nikolaos A
Abstract : Summary: Downregulation of tumor suppression genes by DNA hypermethylation has been proposed as a potential cause of neuroendocrine neoplasm (NEN) formation. In this report, we present a patient simultaneously diagnosed with acute myeloid leukemia (AML) and a metastatic nonfunctioning pancreatic NEN. Because of the two competing diagnoses, he was treated with lanreotide, venetoclax and a long course of the hypomethylating agent decitabine. The AML responded to venetoclax and decitabine treatment while the PanNEN stabilized on lanreotide. Over multiple months of treatment, the PanNEN showed gradual tumor response, consistent with decitabine treatment effect, and the patient remained without disease progression for both malignancies. We believe that some PanNENs can benefit from treatment with hypomethylating agents such as decitabine. To support this, we review the relevant literature and suggest a mechanism for the efficacy of decitabine in our case. Learning points: Neuroendocrine neoplasms are associated with an increased risk of second primary cancers. Epigenetic changes such as hypermethylation and inhibition of tumor suppressor genes might explain the development and behavior of certain NENs. The use of hypomethylating agents such as decitabine might have a role in the treatment of PanNENs. Future studies are needed to confirm that.